Secretagogue stimulation enhances NBCe1 (electrogenic Na(+)/HCO(3)(−) cotransporter) surface expression in murine colonic crypts - Yu, Haoyang (American Physiological Society, 2009)
A Na(+)/HCO(3)(−) cotransporter (NBC) is located in the basolateral membrane of the gastrointestinal epithelium, where it imports HCO(3)(−) during stimulated anion secretion. Having previously demonstrated secretagogue activation of NBC in murine colonic crypts, we now asked whether vesicle traffic and exocytosis are involved in this process. Electrogenic NBCe1-B was expressed at significantly higher levels than electroneutral NBCn1 in colonic crypts as determined by QRT-PCR. In cell surface biotinylation experiments, a time-dependent increase in biotinylated NBCe1 was observed, which occurred with a peak of +54.8% after 20 min with forskolin (P < 0.05) and more rapidly with a peak of +59.8% after 10 min with carbachol (P < 0.05) and which corresponded well with the time course of secretagogue-stimulated colonic bicarbonate secretion in Ussing chamber experiments. Accordingly, in isolated colonic crypts pretreated with forskolin and carbachol for 10 min, respectively, and subjected to immunohistochemistry, the NBCe1 signal showed a markedly stronger colocalization with the E-cadherin signal, which was used as a membrane marker, compared with the untreated control. Cytochalasin D did not change the observed increase in membrane abundance, whereas colchicine alone enhanced NBCe1 membrane expression without an additional increase after carbachol or forskolin, and LY294002 had a marked inhibitory effect. Taken together, our results demonstrate a secretagogue-induced increase of NBCe1 membrane expression. Vesicle traffic and exocytosis might thus represent a novel mechanism of intestinal NBC activation by secretagogues.